Are Scientists Changing their Research Productivity Classes When They Move Up the Academic Ladder? - Kwiek, Marek; Roszka, Wojciech (My University, 2025)
We approach productivity in science in a longitudinal fashion: We track scientists’ careers over time, up to 40 years. We first allocate scientists to decile-based publishing productivity classes, from the bottom 10% to the top 10%. Then, we seek patterns of mobility between the classes in two career stages: assistant professorship and associate professorship. Our findings confirm that radically changing publishing productivity levels (upward or downward) almost never happens. Scientists with a very weak past track record in publications emerge as having marginal chances of becoming scientists with a very strong future track record across all science, technology, engineering, mathematics, and medicine (STEMM) fields. Hence, our research shows a long-term character of careers in science, with one’s publishing productivity during the apprenticeship period of assistant professorship heavily influencing productivity during the more independent period of associate professorship. We use individual-level microdata on academic careers (from a national registry of scientists) and individual-level metadata on publications (from the Scopus raw dataset). Polish associate professors tend to be stuck in their productivity classes for years: High performers tend to remain high performers, and low performers tend to remain low performers over their careers. Logistic regression analysis powerfully supports our two-dimensional results. We examine all internationally visible Polish associate professors in five fields of science in STEMM fields (N = 4,165 with Nart = 71,841 articles).
Keywords: mobility; productivity; productivity classes; longitudinal approach; Polish scientists; top productivity; bottom productivity; academic profession; classificatory approach; tracking scientists over time; science of science; quantitative science studies